2016
DOI: 10.9778/cmajo.20150016
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension screening and follow-up in children and adolescents in a Canadian primary care population sample: a retrospective cohort study

Abstract: This screening measure was frequently done and appeared to be incompletely followed up. Clear guidance is needed; guideline developers should consider reviewing this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…These findings are in line with other data from South Africa [3133]. Previous studies have shown that the strongest risk factor for hypertension in childhood is obesity, male sex, and a family history of hypertension [7, 34]. These findings are supported by our study in which we showed overweight and obese learners to be more likely to be both prehypertensive and hypertensive compared to learners with normal weights as determined by BMI.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in line with other data from South Africa [3133]. Previous studies have shown that the strongest risk factor for hypertension in childhood is obesity, male sex, and a family history of hypertension [7, 34]. These findings are supported by our study in which we showed overweight and obese learners to be more likely to be both prehypertensive and hypertensive compared to learners with normal weights as determined by BMI.…”
Section: Discussionsupporting
confidence: 93%
“…This percentage increased to 87.5 % in a paper by Brady et al (2015), who considered children presenting for both preventative care and acute care visits. These findings have been confirmed in multiple other studies (Stabouli et al 2015;Aliarzadeh et al 2016;Shapiro et al 2012), with recognition rates ranging from 5 % to 67 %. It is clear, then, that a large number of children who meet criteria for hypertension go unrecognized.…”
Section: Recognizing Pediatric Hypertension Can Be Challengingsupporting
confidence: 79%
“…Hypertension monitoring after cardiac surgery (as per guidelines, at least yearly and at all health visits in patients at risk) (27) is important. This is relevant because North American data show that BP screening and follow-up by primary care providers is often suboptimal (43,44).…”
Section: Discussionmentioning
confidence: 99%